The effect of high-intensity interval training (using weights) in the special preparation stage on some physiological variables among young soccer players (Journal of the College of Basic Education, 2022)
High intense periodic training has positive effect in some physiological variables for the young players in football sport which some of which aredeveloping the NON- air phosphorgenic power /abilitydeveloping the NON- air lag tic power/ abilitydeveloping the quadric power/ ability (Energy index)The dissertation sample consisted of 12 players who were chosed by the intentional method and the sample was divided in to two groups, experimental and control and the researcher had set the training program and it lasted for (12) weeksInferencesThe research had inferred that high intense periodic training as it was described in the dissertationHas positive effect in developing the phosphorgenic ability.Has positive effect in developing the NON- oxygenic lag tic ability.Has no moral effect in developing the quadric energy index in its recent form and for 10 weeks period .The used experimental curriculum for the experimental group by weight lifting had positive effect in developing the physiological variables under considerationThe Recommendations Using the high intense periodic training when needing the development of NON- oxygenic & lag tic abilities.Adopting new training programs that depend the known training methods and that by using the foreign resistances for their effective role.Depending new physiological variables related to body building sport for developing the functional work for the players and in accordance to the age stage under consideration.